In what ways do Chinese employees speak up? An exchange approach to supervisor–subordinate guanxi and voice behavior. Issue 3 (4th February 2019) - Wang, Haihua; Wu, Wen; Liu, Yanping; Hao, Shengyue; Wu, Shaoxue
Abstract: Few studies have investigated the effect of supervisor–subordinate guanxi (s–s guanxi ) on employee voice behavior. From a social exchange perspective, the current study sheds light on the effect of s–s guanxi on employee voice behavior through the mediating roles of psychological ownership and psychological empowerment. A theoretical model is developed and empirically tested with a sample of 299 supervisor–subordinate dyads. The results generally support our hypothesis that s–s guanxi can influence employee voice through the mediating roles of psychological ownership and psychological empowerment. However, counter to our hypothesis, we find no support for psychological ownership mediating between s–s guanxi and promotive voice. Implications and contributions are discussed.